Choroidal thickness and high myopia: a case–control study of young Chinese men in Singapore. (21st December 2014) - Gupta, Preeti; Saw, Seang‐Mei; Cheung, Carol Y.; Girard, Michael J. A.; Mari, Jean Martial; Bhargava, Mayuri; Tan, Colin; Tan, Mellisa; Yang, Adeline; Tey, Frederick; Nah, Gerard; Zhao, Paul; et al.
Abstract Purpose To determine the distribution of choroidal thickness (CT) and ocular factors associated with CT in high myopic eyes in comparison with emmetropic eyes of young healthy adults. Methods A case–control study of 648 young, male subjects, including 520 high myopes and 128 emmetropes. Choroidal imaging was performed using enhanced depth imaging spectral domain optical coherence tomography. Images were postprocessed using adaptive compensation for quality enhancement. CT was measured at nine locations, including subfovea and 1.5 and 3 mm nasal, temporal, superior and inferior to fovea. Results The CT at the subfovea was significantly thinner (mean ± standard error: 225.87 ± 5.51 μm) for high myopes compared to emmetropes (375.15 ± 6.58 μm, p < 0.001). Likewise, CT in high myopic group was significantly thinner than emmetropic control group at all locations (p for trend <0.001 for all locations). Distribution of CT showed a markedly different pattern in high myopic eyes (thickest superiorly at 3 mm, 265.97 ± 5.97 μm) and emmetropic eyes (thickest subfoveally, 375.15 ± 6.58 μm). Choroid was thinnest at nasal 3 mm location in both the myopic (108.85 ± 3.97 μm) and emmetropic (238.25 ± 6.72 μm) groups. Among the ocular factors studied, axial length, posterior staphyloma and chorio‐retinal atrophy were the significant predictors of CT. Conclusions Highly myopic eyes have significantly thinner choroid and showed different distribution pattern, compared to emmetropes. Axial length, posterior staphyloma and chorio‐retinal atrophy are the strongest determinants of CT.